Circles of peace: a video analysis of situational group formation and collective third-party intervention in violent incidents - Weenink, Don (The British journal of criminology, 2022)
We seek to understand collective third-party intervention in violent incidents. Based on analyses of 131 video clips captured on mobile phones, we argue that bodily alignment between bystanders creates situational groups that encourage collective de-escalatory action. Qualitative analysis reveals that third parties generate situational groups when they create circular formations, providing greater opportunities to notice each other’s monitoring of the situation while separating those focused on the incident from others just passing by. Statistical analysis shows that the formation of situational groups facilitates the collectivization of de-escalatory action. In contrast to popular but outdated ideas about the dangerous influence of assemblies on individual behaviour (allegedly leading to disorder or apathy), our findings emphasize the self-regulatory, defusing capacity of gatherings.